Pressure reduction on blood flow in aorta coronary sinus conduit - Hussain, Siti Aslina; Tan, Hong Tat; Abdul Hamid, Mohd Ismail; Abdullah, Norhafizah; Idris, Azni (Universiti Putra Malaysia Press, 2012)
Numerical studies of blood flow system of aorta coronary sinus conduit were carried out using ANSYSTM CFD simulation. A different model of conduit, which differs in the inlet diameter, was investigated. The investigated inlet diameters are 3 mm, 4 mm and 5 mm. Pressure drop from 80 mmHg to 15 mmHg was achieved for all the models. The comparison chart was produced to compare the pattern of pressure reduction as well as velocity distribution in each model. From the analysis of coronary sinus conduit, it was found that a narrow tube needs to be incorporated into the conduit produced. This is to induce a venturi effect to reduce the pressure drop of blood within a specific throat length. As conclusion, a model of 3 mm inlet and a throat diameter of 1.13 mm show satisfactory result for pressure reduction from 80 mmHg to 15 mmHg. This particular model also has a lower peak velocity at the inlet zone of the throat section, which is more preferable in terms of Reynolds number.